Strategi Peningkatan Penerimaan Retribusi Pasar Non Tunai (E-Retribusi) Pelayanan Pasar Kabupaten Tabanan - Kadek Orin Sita Maharani Wiardika; Putu Dharmanu Yudartha; Kadek Wiwin Dwi Wismayanti (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2024)
This research discusses the strategy to increase the revenue of non-cash retribution (e-retribution) in Kediri Market, Tabanan Regency. Through analysis of the findings and SWOT analysis, it is concluded that although a strategy has been designed, its implementation has not been optimal. Several shortcomings were identified, including in environmental scanning, strategy formulation, strategy implementation, and evaluation and control. Based on the findings, suggestions were provided to improve the implementation of the strategy, including identification of the quality of employees, adjustment of the mission, periodic strategy development, and increased use of the systems provided. It is expected that by implementing these suggestions, strategy implementation can run more optimally. Abstrak Penelitian ini membahas tentang strategi peningkatan penerimaan retribusi non-tunai (e-retribusi) di Pasar Kediri Kabupaten Tabanan. Melalui analisis hasil temuan dan analisis SWOT, disimpulkan bahwa meskipun strategi telah dirancang, pelaksanaannya belum optimal. Beberapa kekurangan teridentifikasi, termasuk dalam pemindaian lingkungan, perumusan strategi, implementasi strategi, dan evaluasi serta pengendalian. Berdasarkan temuan tersebut, saran-saran diberikan untuk memperbaiki pelaksanaan strategi, termasuk identifikasi kualitas pegawai, penyesuaian misi, pengembangan strategi berkala, dan peningkatan penggunaan sistem yang disediakan. Diharapkan dengan menerapkan saran-saran tersebut, pelaksanaan strategi dapat berjalan lebih optimal. Kata Kunci: Strategi, E-retribusi, Pasar Kediri, Kabupaten Tabanan, Pemindaian Lingkungan, Perumusan Strategi, Implementasi Strategi, Evaluasi, Pengendalian.